Navigating the who, where, what, when, how and why of trauma exposure and response - Hyland, Philip (European journal of psychotraumatology, 2021)
Individual differences in the response to trauma are influenced by numerous contextual factors such as one’s cultural background, the environment in which trauma occurs, the meanings attached to traumatic experiences, and various other social and cultural determinants both before and after traumatic exposure. This special issue of the European Journal of Psychotraumatology presents a series of papers conducted as part of the Collaborative Network for Training and Excellence in Psychotraumatology (CONTEXT); a programme of research which seeks to advance our understanding of the impact of trauma within diverse populations who are highly trauma exposed. Applying a context-specific focus, CONTEXT prioritised working closely with service users and those organisations delivering critical support in the wake of trauma exposure. The seven papers presented in this special issue are divided into those who are exposed to trauma either: (i) directly (survivors of childhood adversity in the USA; LGB youth in Northern Ireland; refugees and asylum seekers in the EU; and members of the general population exposed to conflict in Israel) or (ii) vicariously (fire fighters in the UK, humanitarian aid volunteers in Sudan, and child protection workers in Denmark). Together, findings from these studies demonstrate that social support, in its many different forms, is a universally important factor in the response to trauma. We discuss how traumatic stress can be compounded when, and can thrive within, contexts where necessary social support is absent or inadequate. We also emphasize the importance of recognizing the context specificity of trauma exposure and trauma response, as well as the need for collaboration between psychotrauma researchers and organisations who deliver support to traumatized populations to ensure rapid and effective translation of research findings into practice